Power Struggle Through Digital Communication in Novel Everything, Everything by Nicola Yoon: A Foucauldian Discourse Analysis - Nur Azizah Dwi Safitri; Rahayu Puji Haryanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the dynamics of power struggle through digital communication in the novel Everything, Everything by Nicola Yoon using the Foucauldian discourse analysis approach. This study has three main objectives: first, to analyze the representation of digital communication in the story; second, to examine the construction of power struggle through digital communication in the story; and third, to explore the implications of power struggle in human relations in the digital era as depicted in the novel. The study focuses on how digital communication functions as a medium of power relations, especially in the context of the main character, Madeline Whittier, who relies on digital platforms to interact with the outside world due to her isolation. The method used in this research is descriptive qualitative, based on Michel Foucault's theory of power, knowledge, and discourse. The results of the analysis show that digital communication in Everything, Everything not only facilitates interpersonal relationships, but also becomes an instrument of domination as well as resistance. This study highlights how digital technology mediates emotions, decision- making, and shapes power structures in contemporary society. Through a Foucauldian discourse approach, this study contributes to literary studies and digital communication theory, and bridges the gap between classical discourse analysis and modern technological realities. In addition, the findings offer practical insights for educators, parents, and policy makers in understanding the complexity of digital interactions among teenagers.